A rare case of atypical lipoma in retropharyngeal space and review of literature - Narayana, M. Lakshmi; Mohiyuddin, S. M. Azeem; Viswambharan, Vivek; Gaur, Urvashi; Swethadri, G. Krishnamurthy (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
The term atypical lipoma was introduced to describe the relatively benign course of well-differentiated liposarcomas when they occur in extremities compared to their retroperitoneal counterparts. A 32-year-old lady presented with dysphagia, excessive snoring and difficulty in breathing for three months. On examination, a smooth globular retropharyngeal swelling was seen extending anteriorly till epiglottis obscuring the view of vocal cords. The CECT scan demonstrated features suggestive of a lipomatous lesion with possible sarcomatous change. Excision was done through a transcervical approach and histopathology showed features suggestive of atypical lipoma of retropharyngeal space. As the tumor was removed in toto, adjuvant radiotherapy was not advised. Hence if any swelling in the retropharyngeal space is noted, the probability of soft tissue tumors must be ruled out by a CT/MRI scan before attempting incision and drainage or any other surgical procedure. Postoperative adjuvant radiotherapy is limited to high-grade tumors, incompletely excised tumors and more radiosensitive liposarcoma subtypes such as myxoid sarcomas.